Inclusive pedagogies - restoring agency and voice to the learner - Terry Wrigley (Universidad Autónoma de Madrid, 2015)
For schools serving communities marginalised by poverty or racial / cultural / religious difference, pedagogy involves understanding the relationship between the identities and 'habitas' of the children as developed outside of school, and their experience of school learning. This relationship is problematic for many reasons, which this article attempts to explore